(Invited) Challenges with Quantum Chemistry-Based Screening of Electrochemical Stability of Lithium Battery Electrolytes. (9th September 2015) - Borodin, Oleg; Olguin, Marco; Spear, Carrie; Leiter, Kenneth; Knap, Jaroslaw; Yushin, Gleb; Childs, Adam; Xu, Kang
Abstract : Challenges with the quantum chemistry based-screening of electrochemical stability of solvents and salts with potential applications in lithium batteries are discussed. Initial high throughput screening of carbonate and phosphate-based electrolyte solvents provided insight into first and second reduction and oxidation potentials and reorganization energies of these solvents. It has been found that it was important to include a lithium cation in the screening of semifluorinated solvents. Two reduction pathways has been found for lithium complexed with semifluorinated solvents and salts such as lithium bis(fluorosulfonyl)imide (LiFSI): the low rate defluorination reaction occurring at high potentials and fast solvent or anion reduction occurring at significantly lower potentials. A spontaneous deprotonation of carbonate solvents at the surface of the completely de-lithiated LiNi0.5 Mn1.5 O4 cathode has been found.